Optimalisasi Penerapan Teknologi Akuakultur dalam Upaya Peningkatan Produktivitas di Unit Usaha Budidaya Ikan Gabus Kabupaten Banyuasin - Adli; Prariska, Donny; Lestari, Siti; Sumsanto, Muhammad (Universitas Mataram, 2023)
Aquaculture as an economic and environmentally based business sector has significant development potential. As a complex business, implementing aquaculture requires the role and support of various parties. Business actors in the aquaculture sector generally rely on field knowledge, traditional methods, and individual abilities. The implementation of acculturation systems and technology in current business units needs to be carried out with the right strategy and consistent assistance. This activity aims to increase partner productivity by optimizing the implementation of zero-waste aquaculture systems and technology based on economics and the environment and with appropriate and consistent assistance. The program is implemented using counseling, training, and mentoring methods. Counseling was carried out to partners and cultivation groups in the Banyuasin area regarding the implementation of the planned technology. In the counseling, it was explained that the next activities would be several training sessions and opportunities to receive training for business actors who are currently producing.